Fostering Community Rehabilitation : Ecuador El Niño Emergency Recovery Project - World Bank (Washington, DC, 2012)
During the past decade, Ecuador has suffered multiple natural disasters. It was hard hit by the El Nino phenomenon in 1982 and again in 1998. In addition to the psychological effects on the population, thousands of homes were destroyed, road networks damaged, extensive agricultural areas rendered uninhabitable, and large groups of people lost their livelihoods. Natural disasters place additional strain on a country classified as one of the poorest countries in Latin America with 50.9% of the total population living below poverty line. In response, the World Bank, together with the Inter-American Development Bank and the Corporacion Andina de Fomento, assisted the government to establish the El Nino Emergency Recovery Project. The project utilized social analysis in establishing criteria to ensure the project reached the poorest and to identify mechanisms for community participation. Communities participated in a continuous analysis process during implementation.